Composite containing polyvinyl alcohol and hydrophilic and water-dispersible filler
Patent Information
- Application Number
- JP2019239104
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2019-12-27
- Publication Date
- 2025-02-13
- Estimated Expiration
- 2039-12-27
Smart Images

Figure 0007629165000001 
Figure 0007629165000002 
Figure 0007629165000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a humidity-responsive composite comprising at least one polyvinyl alcohol and at least one hydrophilic, water-dispersible filler, wherein the concentration of the filler is 30% by weight or less, based on the total weight of the composite. [Background technology]
[0002] In the field of hair cosmetics, consumers are demanding hair styling products that can maintain their hairstyle for a long time under high humidity conditions. Currently, many styling products in various forms such as gels, mists, waxes, and creams are used, but there are no products that can meet the above demands.
[0003] Humidity-responsive materials whose properties change depending on relative humidity are known. For example, such materials are disclosed in U.S. Patent No. 6,627,673 (B2) and U.S. Patent No. 8,790,450 (B2). However, they are difficult to use in cosmetics due to safety concerns and lack of cosmetic properties.
[0004] Thus, there is a need for humidity responsive hair cosmetic products that maintain the hairstyle under high humidity conditions and have acceptable cosmetic properties. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] U.S. Patent No. 6,627,673(B2) [Patent Document 2] U.S. Patent No. 8,790,450 (B2) Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide a humidity-responsive material that can be used in hair cosmetics that can not only maintain a hairstyle for a long period of time under high humidity conditions but also impart excellent cosmetic effects to hair. [Means for solving the problem]
[0007] The above object can be achieved by a composite comprising at least one polyvinyl alcohol and at least one hydrophilic and water-dispersible filler, the concentration of the filler being less than or equal to 30% by weight relative to the total weight of the composite.
[0008] The degree of hydrolysis of the polyvinyl alcohol may be 70% or more, preferably 75% or more, more preferably 80% or more, most preferably 85% or more, and less than 100%, preferably 98% or less, more preferably 95% or less, most preferably 90% or less.
[0009] The degree of polymerization of polyvinyl alcohol may be 150 or more, preferably 300 or more, more preferably 500 or more, and most preferably 700 or more, and 2500 or less, preferably 2200 or less, more preferably 2000 or less, and most preferably 1800 or less.
[0010] Polyvinyl alcohol is composed of the following units (I):
[0011] [ka]
[0012] and Optional units (II) of:
[0013] [ka]
[0014] and the unit (II) is absent or present in an amount of 1 mol % or more, preferably 5 mol % or more, more preferably 10 mol % or more, and 20 mol % or less, preferably 18 mol % or less, more preferably 15 mol % or less.
[0015] The hydrophilic and water-dispersible fillers can be selected from inorganic and organic fillers.
[0016] The inorganic filler may be selected from silica (SiO2), iron oxide (Fe3O4) and titanium dioxide (TiO2) particles.
[0017] The organic filler may be cellulose or a derivative thereof, preferably microcrystalline cellulose.
[0018] The concentration of the hydrophilic, water-dispersible filler may be 25% by weight or less, preferably 20% by weight or less, more preferably 15% by weight or less, and most preferably 10% by weight or less, and may be 1% by weight or more, preferably 3% by weight or more, and more preferably 5% by weight or more, based on the total weight of the composite.
[0019] The present invention may also relate to a method of preparing the composite of the present invention, comprising the step of mixing polyvinyl alcohol and a hydrophilic, water-dispersible filler in an aqueous medium, such as water.
[0020] The present invention may also relate to a composition comprising the complex of the present invention in an amount of 1% by weight or more, preferably 2% by weight or more, more preferably 3% by weight or more, and 20% by weight or less, preferably 10% by weight or less, more preferably 5% by weight or less, relative to the total weight of the composition.
[0021] The present invention may also relate to a composition comprising at least one polyvinyl alcohol and at least one hydrophilic, water-dispersible filler, the concentration of the filler being 30% by weight or less, based on the total weight of the polyvinyl alcohol and the filler, and the polyvinyl alcohol and the filler being combined to form a composite.
[0022] The composition according to the invention may be a cosmetic composition for keratinous fibres such as hair, preferably a hair styling composition.
[0023] The present invention may also relate to a method of styling the hair, preferably whilst providing the hair with excellent cosmetic benefits, such as excellent feel of the hair, comprising the step of applying to the hair a complex or a composition according to the present invention.
[0024] The present invention may also relate to a method for storing a hairstyle so that it can be restored under humid conditions, or for maintaining a hairstyle for a long period of time under humid conditions, comprising the step of applying to the hair a complex or a composition according to the present invention.
[0025] The present invention may also relate to the use of a combination of at least one polyvinyl alcohol and at least one hydrophilic, water-dispersible filler, wherein the concentration of the filler is 30% by weight or less, based on the total weight of the polyvinyl alcohol and the filler, to form a humidity-responsive composite. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] As a result of extensive investigations, the present inventors have discovered that a hair cosmetic having a good balance between (i) the property of maintaining a hairstyle for a long period of time under high humidity conditions and (ii) good hair cosmetic effects (such as excellent hair feel) can be provided by a complex comprising at least one type of polyvinyl alcohol and at least one type of hydrophilic, water-dispersible filler, the concentration of the filler being 30 mass % or less relative to the total mass of the complex.
[0027] Thus, one aspect of the present invention is a composite comprising at least one polyvinyl alcohol and at least one hydrophilic, water-dispersible filler, the concentration of the filler being 30% by weight or less, relative to the total weight of the composite.
[0028] The complex of the present invention will now be described in more detail.
[0029] [Complex] The composite of the present invention comprises at least one polyvinyl alcohol and at least one hydrophilic and water-dispersible filler, the concentration of the filler must be less than or equal to 30% by weight based on the total weight of the composite. Preferably, the composite consists essentially of or consists of at least one polyvinyl alcohol and at least one hydrophilic and water-dispersible filler.
[0030] The composite can be prepared from a solution comprising polyvinyl alcohol and a hydrophilic, water-dispersible filler in an aqueous medium, i.e., water and optionally a water-soluble solvent. For example, the composite can be prepared by mixing polyvinyl alcohol and a hydrophilic, water-dispersible filler in an aqueous medium, such as water.
[0031] Among the water-soluble solvents, mention may be made in particular of alcohols, for example lower monohydric alcohols containing from 1 to 5 carbon atoms, such as ethanol and isopropanol, glycols containing from 2 to 8 carbon atoms, such as ethylene glycol, propylene glycol, 1,3-butylene glycol, and dipropylene glycol, C3 and C4 ketones, and C2-C4 aldehydes.
[0032] The composites of the present invention can be considered as aggregates of polyvinyl alcohol and hydrophilic, water-dispersible fillers, for example, covalently bonded assemblies of polyvinyl alcohol and hydrophilic, water-dispersible fillers.
[0033] The complex has humidity responsiveness. Therefore, the complex can maintain the hairstyle for a long time under high humidity conditions. Furthermore, the complex can memorize the hairstyle so that the hairstyle can be restored to its original style under high humidity conditions. Therefore, even if the hair is disturbed after applying the complex to the hair, the hair will return to its original style under high humidity conditions.
[0034] Furthermore, in addition to good hairstyle retention properties, the complexes can provide hair with excellent cosmetic benefits, such as softness, smoothness, and ease of detangling.
[0035] In addition, since the complex contains water-soluble polyvinyl alcohol, the complex can be easily washed off from hair with water.
[0036] The total concentration of polyvinyl alcohol and hydrophilic water-dispersible filler may be 70% by weight or more, preferably 80% by weight or more, more preferably 90% by weight or more, and most preferably 100% by weight, based on the total weight of the composite.
[0037] The complex may be present in a composition, preferably a cosmetic composition for keratinous fibers such as hair, more preferably a hair styling composition, in an amount of 1% by weight or more, preferably 2% by weight or more, more preferably 3% by weight or more, and 20% by weight or less, preferably 10% by weight or less, more preferably 5% by weight or less, based on the total weight of the composition.
[0038] [Polyvinyl alcohol] The composite of the present invention comprises at least one polyvinyl alcohol.
[0039] Polyvinyl alcohol is a polymer having vinyl alcohol units of the formula:
[0040] [ka]
[0041] Polyvinyl alcohol can be obtained by polymerizing vinyl esters to obtain a polymer by a well-known method, and then hydrolyzing the polymer. In the hydrolysis step, generally, an acid or a base is used. Preferably, a base is used in the hydrolysis step. The completely hydrolyzed polymer may be used as the polyvinyl alcohol of the present invention.
[0042] Any suitable polymerization method may be used, examples of which include solution polymerization, bulk polymerization, and suspension polymerization.
[0043] Examples of vinyl esters include vinyl acetate, vinyl formate, vinyl propionate, vinyl butyrate, vinyl pivalate, vinyl laurate, vinyl stearate, and vinyl benzoate.
[0044] The degree of hydrolysis and the degree of polymerization of the polyvinyl alcohol can be appropriately selected depending on the intended use.
[0045] The degree of hydrolysis may be 70% or more, preferably 75% or more, more preferably 80% or more, most preferably 85% or more, and less than 100%, preferably 98% or less, more preferably 95% or less, most preferably 90% or less. The degree of hydrolysis can be controlled by any suitable known method. Generally, the degree of hydrolysis can be measured according to JIS K6726.
[0046] The degree of polymerization may be 150 or more, preferably 300 or more, more preferably 500 or more, and most preferably 700 or more, and 2500 or less, preferably 2200 or less, more preferably 2000 or less, and most preferably 1800 or less. Generally, the degree of polymerization can be measured according to JIS K6726.
[0047] Most preferably, the vinyl ester may be vinyl acetate. Thus, the polyvinyl alcohol contained in the composite of the present invention may be a polymer prepared by polymerizing vinyl acetate and hydrolyzing the resulting product. Thus, polyvinyl alcohol may be a polymer prepared by polymerizing vinyl acetate and hydrolyzing the resulting product. The polyvinyl alcohol may be a polymer prepared by polymerizing vinyl acetate and hydrolyzing the resulting product. Thus, polyvinyl alcohol may be a polymer prepared by polymerizing vinyl acetate and hydrolyzing the resulting product.
[0048] [ka]
[0049] and Optional units (II) of:
[0050] [ka]
[0051] The polymer may be a polymer having the formula:
[0052] In a preferred embodiment, the unit (II) is absent or present in an amount of 1 mol% or more, preferably 5 mol% or more, more preferably 10 mol% or more, and 20 mol% or less, preferably 18 mol% or less, more preferably 15 mol% or less. For example, when the unit (II) is present in an amount of 5 mol%, the degree of hydrolysis is 95%. The polyvinyl alcohol may have an average molecular weight (Mw) of 10000 or more, preferably 12000 or more, more preferably 15000 or more, and 500000 or less, preferably 300000 or less, more preferably 200000 or less.
[0053] Derivatives of polyvinyl alcohol, such as anionically modified polyvinyl alcohol and cationically modified polyvinyl alcohol, may be used in the present invention. Examples of anionically modified polyvinyl alcohol include polyvinyl alcohol modified with carboxylic acid, undecylenic acid, and / or sulfonic acid. For example, carboxylic acid modified polyvinyl alcohol can be prepared by introducing a compound containing a carboxy group into polyvinyl alcohol by any suitable known method. Examples of cationically modified polyvinyl alcohol include polyvinyl alcohol modified with ammonium, sulfonium, and / or amino groups.
[0054] Most preferably, "SELVOL™ (Celvol®) polyvinyl alcohol" sold by SEKISUI Co., Ltd. may be used as the polyvinyl alcohol.
[0055] The concentration of polyvinyl alcohol may be 70% by mass or more, preferably 75% by mass or more, more preferably 80% by mass or more, even more preferably 85% by mass or more, even more preferably 90% by mass or more, and most preferably 95% by mass or more, and may be 99% by mass or less, preferably 97% by mass or less, and more preferably 96% by mass or less, based on the total mass of the composite.
[0056] [Hydrophilic and water-dispersible filler] The composite of the present invention comprises at least one hydrophilic and water-dispersible filler.
[0057] According to the invention, to determine whether a filler is hydrophilic or hydrophobized, the test defined below can be carried out: A test tube with a diameter of 20 mm is filled with 20 ml of water. 2 g of filler are added to the test tube without shaking and the behavior of the filler is observed for a maximum of 5 minutes. If the filler remains completely on the surface, it is considered "hydrophobic". In the opposite case, it is considered "hydrophilic".
[0058] Also, according to the present invention, the term "water-dispersible" means that the filler forms a stable particulate suspension or dispersion in water at a concentration of 5% by weight at 25°C. The average particle size of the particles constituting the dispersion may be, for example, less than 1 μm, more generally in the range of 5 nm to 400 nm, for example 10 nm to 250 nm. These particle sizes can be measured by light scattering methods.
[0059] The term "filler" should be understood to mean colorless or white particles that are solid at room temperature and atmospheric pressure and, according to the invention, do not dissolve in water, even if the water is brought to a temperature higher than room temperature.
[0060] The filler can be selected from inorganic and organic fillers. When the filler is an organic filler, it is a polymeric organic filler. The filler can be any shape, such as platelet-shaped, spherical and oval particles, regardless of their crystallographic morphology (e.g. lamellar, cubic, hexagonal and orthorhombic).
[0061] As used herein, the term "organic filler" means a filler comprising one or more organic compounds, optionally coated with at least one other organic or inorganic compound.
[0062] As used herein, the term "inorganic filler" means a filler comprising one or more inorganic compounds, optionally coated with at least one other organic or inorganic compound.
[0063] Examples of inorganic fillers include fillers containing or consisting of a material selected from talc, mica, silica, glass microcapsules, titanium dioxide, iron oxide (α-Fe2O3, γ-Fe2O3, Fe3O4, FeO), zinc oxide, magnesium aluminum silicate, trimethylsiloxysilicate, kaolin, bentone, calcium carbonate, magnesium hydrogen carbonate, hydroxyapatite, boron nitride, fluorophlogopite, sericite, calcined talc, calcined mica, calcined sericite, synthetic mica, lauroyl lysine, metal soap, bismuth oxychloride, barium sulfate, and magnesium carbonate. In other words, the inorganic filler may be particles of talc, mica, silica, glass microcapsules, titanium dioxide, iron oxide (α-Fe2O3, γ-Fe2O3, Fe3O4, FeO), zinc oxide, magnesium aluminum silicate, trimethylsiloxysilicate, kaolin, bentone, calcium carbonate, magnesium bicarbonate, hydroxyapatite, boron nitride, fluorophlogopite, sericite, calcined talc, calcined mica, calcined sericite, synthetic mica, lauroyl lysine, metal soaps, bismuth oxychloride, barium sulfate, or magnesium carbonate.
[0064] The inorganic filler may be optionally surface-treated to be hydrophilic. The inorganic filler may also be optionally coated. For example, the inorganic filler may be coated with alumina, titanium dioxide, silica, aluminum oxide, and / or barium sulfate, such as TiO2 / silica, mica / TiO2, silica / TiO2, and complexes of silica and TiO2 / TiO2.
[0065] The fillers may be in lamellar or non-lamellar form.
[0066] More preferably, the inorganic filler may be silica (SiO2) particles, iron oxide (Fe3O4) particles, and titanium dioxide (TiO2) particles.
[0067] Examples of organic fillers include cellulose powder, (meth)acrylic or (meth)acrylate powders, such as polymethyl methacrylate powders, e.g. Polytrap®, polyacrylonitrile powders, organopolysiloxane powders, polyamide powders, e.g. Nylon® powders, poly-β-alanine powders, polyethylene powders, fluoroethylene powders, lauroyl lysine, starch, hollow polymeric microspheres, e.g. those containing (alkyl)acrylates, e.g. polyvinylidene chloride / acrylonitrile, e.g. Expancel®, metal soaps derived from organic carboxylic acids containing 8 to 22 carbon atoms, e.g. zinc stearate, magnesium stearate, lithium stearate, zinc laurate, magnesium myristate, and fillers composed of polyurethane powders.
[0068] In a preferred embodiment, the hydrophilic and water-dispersible filler according to the present invention may be a cellulose powder.
[0069] According to the present invention, the term "cellulose" refers to any polysaccharide compound having in its structure a sequence of glucose residues linked together via β-1,4 bonds, and in addition to unsubstituted cellulose, derivatives thereof may be used, such as cellulose ethers, cellulose esters and cellulose ester ethers, such as carboxymethylcellulose, hydroxyethylcellulose and hydroxypropylmethylcellulose.
[0070] In particular, the hydrophilic and water-dispersible filler according to the present invention may be microcrystalline or nanocrystalline cellulose, preferably microcrystalline cellulose.
[0071] Microcrystalline cellulose is a purified, partially depolymerized cellulose obtained from fibrous plant material as a pulp.
[0072] The microcrystalline cellulose may be in the form of particles, the particles preferably having an average particle size of less than or equal to 50 μm, preferably less than or equal to 10 μm, more preferably less than 1 μm. Average particle size means the volume-average particle size.
[0073] In another embodiment, the microcrystalline cellulose may be in the form of fibers, and the fibers preferably have an average fiber diameter of 2 to 5 nm, where average fiber diameter refers to the volume average fiber diameter.
[0074] Microcrystalline cellulose is the isolated crystalline portion of cellulose fibers derived from wood pulp and may preferably be used in colloidal (i.e., co-processed with a soluble hydrocolloid) or non-colloidal form.
[0075] In one embodiment, the microcrystalline cellulose can be used in colloidal form, i.e., in the form of rod-shaped particles, with a particle size of less than 1 μm. The initial viscosity is preferably selected in the range of 30 to 150 cps as a 1 to 3 wt% dispersion. Even more preferably, (a) the microcrystalline cellulose additionally has a sieve fraction of +60 mesh of 0.1% by weight or less and +325 mesh of 75% by weight or less.
[0076] (a) Microcrystalline cellulose can be used alone or in the form of a mixture with sodium carboxymethylcellulose as co-processed microcrystalline cellulose.
[0077] More preferably, the microcrystalline cellulose is "Avicel® PH Microcrystalline Cellulose" sold by FMC Corporation and "Microcrystalline Cellulose" sold by ACCENT.
[0078] The concentration of the hydrophilic and water-dispersible filler should be 30% by weight or less based on the total weight of the complex. If the complex contains more than 30% by weight of the hydrophilic and water-dispersible filler, the complex cannot achieve a good balance between hairstyle retention properties and hair cosmetic effects.
[0079] The concentration of the hydrophilic, water-dispersible filler may be 25% by weight or less, preferably 20% by weight or less, more preferably 15% by weight or less, and most preferably 10% by weight or less, and may be 1% by weight or more, preferably 3% by weight or more, and more preferably 5% by weight or more, based on the total weight of the composite.
[0080] [Composition] The present invention may also relate to a composition comprising at least one polyvinyl alcohol and at least one hydrophilic, water-dispersible filler, the concentration of the filler being 30% by weight or less, based on the total weight of the polyvinyl alcohol and the filler, and the polyvinyl alcohol and the filler being combined to form a composite.
[0081] The composition may preferably be a cosmetic composition for keratinous fibres such as hair, preferably a hair styling composition.
[0082] The compositions according to the invention may also contain ingredients commonly used in cosmetics, such as vitamins, fragrances, pearlescent agents, thickeners, gelling agents, trace elements, analgesics, sequestering agents, basifying or acidifying agents, preservatives, sunscreens, surfactants, antioxidants, anti-hair loss agents, anti-dandruff agents, propellants or ceramides, or mixtures thereof. Naturally, the skilled artisan will ensure that this or these optional additional compounds, and / or their amounts, are selected such that the advantageous properties of the compositions according to the invention are not, or are not substantially, impaired by the envisaged addition.
[0083] The compositions according to the invention may in particular have the form of an aqueous, alcoholic or aqueous / alcoholic solution or suspension, an oily suspension or solution, an emulsion or dispersion with a liquid or semi-liquid viscosity obtained by dispersing a fatty phase in an aqueous phase (O / W) or vice versa (W / O), a dispersion or emulsion with a soft viscosity, an aqueous or aqueous / alcoholic or oily (anhydrous) gel, or of microcapsules or microparticles, or of vesicular dispersions of ionic and / or non-ionic type.
[0084] A person skilled in the art will be able to select the appropriate cosmetic form and its preparation method based on his general knowledge, taking into account, on the one hand, the nature of the components used and, on the other hand, the use envisaged for the composition.
[0085] In particular, the compositions according to the invention can be used in the hair field, especially for retaining the shape of the hairstyle or shaping the hair.
[0086] The hair composition may preferably be a shampoo, a gel, a hair lotion, a blow dry lotion, a fixing and styling composition (such as a lacquer or a spray), etc. The lotion may be packaged in various forms, in particular in a spray, a pump dispenser or an aerosol container, to provide for application of the composition in a spray or foam form.
[0087] [Method and Use] The complexes according to the invention are preferably intended for use in cosmetic compositions for keratinous fibres such as hair, preferably hair styling compositions.
[0088] The complex or composition according to the present invention preferably provides excellent cosmetic benefits to the hair (such as excellent feel of the hair) and may also be used in a method of styling the hair, which method comprises applying a complex or composition according to the present invention to the hair.
[0089] In particular, the complex or composition according to the present invention may be used in a method for storing a hairstyle so that the hairstyle can be restored under humid conditions, the method comprising the step of applying a complex or composition according to the present invention to the hair. The complex or composition according to the present invention may also be used in a method for maintaining a hairstyle under humid conditions, the method comprising the step of applying a complex or composition according to the present invention to the hair. The complex or composition according to the present invention may also be used in a method for restoring a hairstyle under humid conditions, the method comprising the step of applying a complex or composition according to the present invention to the hair and subjecting the hair to humid conditions for restoration.
[0090] The present invention may also relate to the use of a combination of at least one polyvinyl alcohol and at least one hydrophilic, water-dispersible filler, the concentration of the filler being 30% by weight or less, based on the total weight of the polyvinyl alcohol and the filler, for forming a humidity-responsive composite. Another aspect of the present invention is a combination of at least one polyvinyl alcohol and at least one hydrophilic, water-dispersible filler, the concentration of the filler being 30% by weight or less, based on the total weight of the polyvinyl alcohol and the filler, for use in forming a humidity-responsive composite.
[0091] The present invention may also relate to the use of a complex or composition according to the invention for styling the hair, preferably while providing the hair with excellent cosmetic results, such as excellent feel of the hair.
[0092] In particular, the present invention may also relate to the use of a complex or composition according to the invention (i) for storing a hairstyle so that it can be restored under humid conditions, or (ii) for maintaining a hairstyle under humid conditions.
[0093] The complex or composition according to the present invention can maintain a hairstyle under high humidity conditions. The complex or composition according to the present invention can also restore a hairstyle to its original style under high humidity conditions. Furthermore, the complex or composition according to the present invention can impart excellent cosmetic effects to hair. EXAMPLES
[0094] The present invention will now be described in more detail with reference to examples, which should not be construed as limiting the scope of the present invention.
[0095] Example 1 Properties of membranes made from the composites of the present invention and comparative examples In this example, microcrystalline cellulose was used as a hydrophilic and water-dispersible filler. As described below, the membrane of the present invention was prepared from the composite of the present invention obtained from the "Inventive Formulation" containing polyvinyl alcohol (PVA) and microcrystalline cellulose, the concentration of which is within the range specified in the present invention. Comparative membranes were prepared from the comparative composite obtained from the "Comparative Formulation 1" containing only PVA. Comparative membranes were also prepared from the comparative composite obtained from the "Comparative Formulation 2" and "Comparative Formulation 3" containing PVA and microcrystalline cellulose, the concentration of which is outside the range specified in the present invention. The prepared composite membranes were compared with respect to shape memory properties.
[0096] 1.1 Preparation of formulations containing polyvinyl alcohol 20 g of polyvinyl alcohol (PVA) pellets were added to 180 g of distilled water so that the concentration of PVA was 10% by mass, and the mixture was stirred in a water bath at 80° C. for several hours until the polyvinyl alcohol pellets were completely dissolved. After the solution became homogeneous, it was cooled to room temperature to obtain Comparative Example Formulation 1.
[0097] 1.2 Preparation of formulations containing PVA and microcrystalline cellulose PVA pellets and microcrystalline cellulose were added to water to obtain a total concentration of PVA and microcrystalline cellulose of 10% by weight. The ratio of PVA and microcrystalline cellulose was varied to obtain a concentration of microcrystalline cellulose in the composite of 25% by weight (inventive formulation), 50% by weight (comparative formulation 2), or 75% by weight (comparative formulation 3). The mixture was stirred at 80° C., and then cooled with stirring. The mixture was sonicated for 30 minutes to remove bubbles.
[0098] 1.3 Preparation of membranes of the present invention and comparative examples Each of the formulations of the present invention and the comparative formulations was placed on a plastic disk having a diameter of 10 cm. Each disk was placed in an oven at 60° C. overnight to form a film having a thickness of about 0.1 mm.
[0099] 1.4 Comparison of shape memory properties of the membranes of the present invention and comparative examples Each of the membranes of the present invention and the comparative example was cut into a 0.5 x 6 cm piece. The membrane was twisted to form a curl and fixed to a glass rod with a clip. The glass rod was left in a 120 ° C oven for 30 minutes to perform shape memory processing. The glass rod was removed from the oven and cooled to room temperature. A weight of 5 g was attached to the membrane to stretch it, and the stretched membrane was left overnight. The weight was removed and the length of the membrane was measured (this length corresponds to the "length of the membrane before humidification" and was called "L1"). The membrane was then left in a humid chamber (humidity 80% to 90%) for 6 hours. The membrane was removed from the chamber and the length of the membrane was measured (this length corresponds to the "length of the membrane after humidification" and was called "Lt"). The percentage of shape memory property (% of SMP) was calculated by the following formula: "[(L1-Lt) / L1] x 100".
[0100] 1.5 Results The results obtained are shown in Table 1.
[0101] [Table 1]
[0102] Only the composites prepared from the formulations of the present invention could form films with high "% of SMP". This means that only the composites of the present invention containing PVA and microcrystalline cellulose (hydrophilic and water-dispersible fillers) could return to their original shape after being exposed to high humidity conditions. In other words, only the composites of the present invention have high humidity responsiveness. It was also demonstrated that the concentration of the hydrophilic and water-dispersible filler is important, and that when the concentration of the hydrophilic and water-dispersible filler is high (such as 50% by weight), shape memory properties are not imparted. Furthermore, it was demonstrated that when the concentration of the hydrophilic and water-dispersible filler is too high (such as 75% by weight), a film cannot be formed.
[0103] Example 2 Effect of the complexes of the present invention and the comparative examples when applied to hair In this example, microcrystalline cellulose was also used as a hydrophilic and water-dispersible filler. Similar to Example 1, inventive and comparative formulations were prepared according to the amounts of PVA, microcrystalline cellulose, and water shown in Table 2.
[0104] As described below, the formulations of the present invention and the comparative examples were each applied to hair and compared for their hairstyle retention properties under high humidity conditions (shape memory properties and curl retention properties) and hair cosmetic effects.
[0105] 2.1 Shape memory properties 0.30 g of each of the formulations of the present invention and the comparative example was applied to 1 g of Chinese bleached hair swatches. A hair iron (16 mm diameter) was used at 170-180°C for 20 seconds to create a shape. The hair swatches were stretched overnight with a weight of 10-15 g attached. After removing the weight, the length of the hair swatches was measured (this length corresponds to the "hair length before humidification" and was designated "L1"). The stretched hair swatches were placed in a humid chamber (humidity 75-85%) at 30°C for 6 hours. The hair swatches were removed from the chamber and their length was measured (this length corresponds to the "hair length after humidification" and was designated "Lt"). The percentage of shape memory property (%SMP) was calculated by the following formula: "[(L1-Lt) / L1]x100".
[0106] 2.2 Curl retention properties 0.20 g of each of the inventive and comparative formulations was applied to 2.7 g of Chinese bleached hair swatches. A hair iron (16 mm diameter) was used at 170-180°C for 20 seconds to create a shape. The number of curls was counted (this number corresponds to the "curl number before humidification" and was designated "N1"). The hair swatches were placed in a humid chamber (75-85% humidity) at 30°C for 6 hours. The hair swatches were removed from the chamber and the number of curls was counted (this number corresponds to the "curl number after humidification" and was designated "Nt"). The percentage of curl retention was calculated by the following formula: "100-[(N1-Nt) / N1x100]".
[0107] 2.3 Hair beauty effects The cosmetic effect of the hair to which each of the formulations of the present invention and the comparative example was applied was evaluated based on the smooth feel, and the criteria were as follows: "Very good" means that the cosmetic effect of the hair was completely acceptable, "Good" means that the cosmetic effect of the hair was moderately acceptable, and "Poor" means that the cosmetic effect of the hair was unacceptable.
[0108] 2.4 Results The results obtained are shown in Table 2.
[0109] [Table 2]
[0110] Only formulations A and B of the present invention were able to achieve a good balance between (i) the ability to restore hair shape under humid conditions (i.e., high "% SMP") and maintain hairstyle for a long time under humid conditions (i.e., high "% curl retention") and (ii) excellent cosmetic effect. This balance was not achieved by comparative formulations A-E. In particular, this good balance was not achieved by comparative formulation C, in which the concentration of microcrystalline cellulose (hydrophilic and water-dispersible filler) was 37.5% by weight relative to the total weight of the complex, demonstrating that this good balance can be achieved when the concentration of hydrophilic and water-dispersible filler is 30% by weight or less relative to the total weight of the complex.
Claims
1. A cosmetic hair styling composition for keratin fibers in the form of an aqueous or alcoholic solution or an aqueous, alcoholic or oily gel, containing a complex comprising at least one polyvinyl alcohol and at least one hydrophilic and water-dispersible filler, the concentration of said filler being 30% by weight or less relative to the total weight of said complex, said hydrophilic and water-dispersible filler being microcrystalline cellulose, and said complex being a covalently bonded aggregate of said polyvinyl alcohol and said hydrophilic and water-dispersible filler (excluding compositions comprising mandarin orange extract).
2. 2. The cosmetic hair styling composition according to claim 1, wherein the degree of hydrolysis of the polyvinyl alcohol is at least 70%, preferably at least 75%, more preferably at least 80%, most preferably at least 85%, and less than 100%, preferably at most 98%, more preferably at most 95%, most preferably at most 90%.
3. 3. The cosmetic hair styling composition according to claim 1 or 2, wherein the degree of polymerization of the polyvinyl alcohol is 150 or more, preferably 300 or more, more preferably 500 or more, most preferably 700 or more, and is 2500 or less, preferably 2200 or less, more preferably 2000 or less, most preferably 1800 or less.
4. The polyvinyl alcohol comprises the following units (I): 【Chemistry 1】 and Optional units (II) of: 【Chemistry 2】 4. The cosmetic hair styling composition according to claim 1, wherein said unit (II) is absent or present in an amount of at least 1 mol%, preferably at least 5 mol%, more preferably at least 10 mol%, and at most 20 mol%, preferably at most 18 mol%, more preferably at most 15 mol%.
5. 5. The cosmetic hair styling composition according to claim 1, wherein the concentration of the hydrophilic and water-dispersible filler is 25% by weight or less, preferably 20% by weight or less, more preferably 15% by weight or less, most preferably 10% by weight or less, and 1% by weight or more, preferably 3% by weight or more, more preferably 5% by weight or more, based on the total weight of the complex.
6. 6. The cosmetic hair styling composition according to any one of claims 1 to 5, comprising said complex in an amount of at least 1% by weight, preferably at least 2% by weight, more preferably at least 3% by weight, and at most 20% by weight, preferably at most 10% by weight, more preferably at most 5% by weight, relative to the total weight of the composition.
7. 7. A method for styling hair, preferably whilst imparting excellent cosmetic benefits to the hair, such as excellent feel of the hair, comprising the step of applying to the hair a composition according to any one of claims 1 to 6.
8. 7. A method for storing a hairstyle so that it can be restored under humid conditions, or for maintaining a hairstyle for a long period of time under humid conditions, comprising the step of applying a composition according to any one of claims 1 to 6 to the hair.
Citation Information
Patent Citations
Coating film type pack material
JP1985067404A
Transparent material
JP1988308069A
Flowable gelatinous material and method for manufacturing the same
JP2001142389A
Hair dressing preparation
JP2001316228A
Polyvinyl alcohol film
JP2002146053A